Thermally Solvent-Free Cross-Linked pH/Thermosensitive Hydrogels as Smart Drug Delivery Systems - Sanda Bucatariu; Bogdan Cosman; Marieta Constantin; Gabriela Liliana Ailiesei; Daniela Rusu; Gheorghe Fundueanu (Gels)
An imbalance in the body’s pH or temperature may modify the immune response and result in ailments such as autoimmune disorders, infectious diseases, cancer, or diabetes. Dual pH- and thermo-responsive carriers are being evaluated as advanced drug delivery microdevices designed to release pharmaceuticals in response to external or internal stimuli. A novel drug delivery system formulated as hydrogel was developed by combining a pH-sensitive polymer (the “biosensor”) with a thermosensitive polymer (the delivery component). Thus, the hydrogel was created by cross-linking, using a solvent-free thermal approach, of poly(N-isopropylacrylamide-co-N-hydroyethyl acrylamide), P(NIPAAm-co-HEAAm), and poly(methylvinylether-alt-maleic acid), P(MVE/MA). The chemical structure of the polymers and hydrogels was analyzed using Fourier-transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR) spectroscopies. The pH/thermosensitive hydrogel loses its thermosensitivity under physiological conditions but, remarkably, can recover the thermosensitive capabilities when certain physiologically active biomolecules, acting as triggering agents, electrostatically interact with pH-sensitive units. Our research aimed to develop a drug delivery system that could identify the disturbance of normal physiological parameters and instantaneously send a signal to thermosensitive units, which would collapse and modulate the release profiles of the drug.